Functional‐coefficient regression models with GARCH errors. Issue 3 (8th March 2021) - Yuan, Yuze; Bai, Lihua; Jiang, Jiancheng
Abstract: The GARCH models are widely used to model various financial data with nonlinearity and heteroscedasticity structures. In this article, we propose a functional‐coefficient regression model with GARCH( r,   s ) errors to model these kinds of data. To deal with the effect of heteroscedasticity, we introduce a two‐step approach to estimating the unknown coefficient functions and the volatility, which results in unweighted and weighted local linear estimators. Asymptotic properties of the proposed estimators are established. Our results demonstrate that the weighted estimator is more efficient than the unweighted one, and the functional coefficients can be estimated by the weighted estimator as if the volatility was known. Both simulations and real data examples support our theoretical results. In particular, when there are GARCH effects, our two‐step estimator mimics the oracle estimator, with the true volatility being known in advance. Résumé: Les modèles GARCH sont couramment utilisés pour modéliser diverses données financières à queues lourdes avec des structures non linéaires et hétéroscédastiques. Les auteurs proposent une régression à coefficients fonctionnels avec des erreurs GARCH(r, s) pour modéliser des données de ce type. Afin de gérer l'hétéroscédasticité, les auteurs introduisent une approche en deux étapes pour estimer les coefficients inconnus puis la volatilité, ce qui conduit à des estimateurs linéaires locaux, pondérés ou non, dont les propriétés asymptotiques sont établies. L'estimateur pondéré s'avère plus efficace que celui qui ne l'est pas, au point où les coefficients fonctionnels peuvent être estimés aussi bien que si la volatilité était connue. Les auteurs présentent les simulations et l'analyse de données réelles qui supportent leurs résultats théoriques. En présence d'effets GARCH, notamment, l'estimateur à deux étapes imite l'estimateur oracle dans le cas où la vraie volatilité serait connue d'avance.